Tajna notatka Wydziału Zagranicznego KC PPR o problemach repatriacyjnych Polaków z ZSRR z 5 grudnia 1947 roku - Marciniak, Wojciech (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2018)
In December of 1947 in Foreign Department of Central Committee of Polish Workers’ Party appeared a note concerning difficulties with repatriation of Poles from the USSR. They concerned mainly relatives of members of the ruling party. The note contains descriptions of many formal problems concerning arrival of Polish citizens from the USSR. The document was created when the question of repatriation in Polish-Soviet relations was in fact frozen. Nonetheless, the problems described in the document prove that repatriation remained important issue for communist party in Poland.